Effect of Implementing a Training Program on the Performance of Primary School Teachers Regarding Disaster Management in Al Malikeyeh - Syria - Abozeed, Basem Essa; Toama, Zakia Toma; Mohamed, Amina Ahmad; El-Fattah Ibrahim, Alyaa Farouk Abd (International Journal of Innovative Research in Medical Science, 2019)
Background: Disasters are a global problem, concern every community and no community is immune from it, schools all over the world suffer from disasters, which affect children health and safety. Teachers play essential roles in child protection so, teachers’ training is very significant for effective school disaster management. The study aimed to evaluate. The effectiveness of implementing a training program on the performance of primary school teachers in Al Malikeyeh regarding disaster management. Methods: Design: Quasi-experimental design. Setting: the current study conducted in six primary schools at Al-Malikeyeh distracts. Sample: 78 school teachers. Tool of the study: Teacher's knowledge and practice about disaster management structured interview questionnaire which contained three parts: part (I): Socioeconomic data, part (II): knowledge of the teachers, part (III): practice of the teachers .Results: about 35.8% of teachers had good knowledge pre program; meanwhile post and follow up the program this percent was increased respectively 87.2 % and79.5%. Also the findings observed that 30.8% of teachers had satisfactory practice, whereas, respectively 84.6% and 76.9 of them gained satisfactory disaster management practice post and follow up the program,. Conclusion: Implementing the training program had statistically significant improvement on knowledge and skills of primary school teachers in Al-Malikyeh regarding disaster management. Recommended: Training programs and workshops about disaster issues should be organized for the school teachers and key teams on regular basis, in addition to, awareness campaigns should be implementing with employing mass and social media technologies.